Purification, physicochemical and formulation properties of shea (Vitellaria Paradoxa) Gum. - Oppong, Esther Eshun (2012)
A Thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the Degree of Master of Philosophy in Pharmaceutics, June-2012